A Comparison of Endovascular Versus Open Repair of Popliteal Artery Aneurysms: An Updated Meta-Analysis. (May 2020) - Tian, Yu; Yuan, Biao; Huang, Zhiyong; Zhang, Ning
Objective: Traditionally, popliteal artery aneurysms (PPAs) were treated via open repair (OR). However, more recently endovascular repair (EVR) approaches have become more common for the treatment of PPAs. The present meta-analysis therefore sought to conduct an up-to-date review of studies comparing the relative safety and efficacy of these 2 repair strategies. To that end, patient outcomes including primary patency, operating time, hospital stay duration, and re-intervention, amputation, and graft occlusion within 30 days were compared for these OR and EVR approaches. Methods: Studies in which OR and EVR were compared as treatments for PPAs were identified through systematic searching of the PubMed and Embase databases. Any studies either analyzing only one of these treatments in isolation or analyzing <5 patients were not included in this analysis. For all relevant studies, patient demographic information and outcome details were compiled. Risk of bias was analyzed using a modified Newcastle-Ottawa Scale. The odds ratios, mean differences, and hazard ratios (HRs) for patient outcomes were estimated using a random-effects model. Results: In total, we identified 17 relevant studies including a single randomized controlled trial and 16 retrospective cohort studies, incorporating 6887 total cases (1662 EVR and 5225 OR). The quality of evidence for all measured outcomes was deemed to be very low or low according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Rates of primary patency were found to be significantly higher for patients treated via OR relative to those treated via EVR (HR = 1.60; 95% confidence interval [CI]: 1.12-2.30; P = .03). Operative and hospitalization durations, in contrast, were significantly lower for patients treated via EVR. Patients treated via EVR also experienced significantly higher rates of graft thrombosis and reintervention within 30 days relative to patients treated via OR. However, no significant differences were observed between treatments with respect to rates of patient amputation (OR = 1.01; 95% CI: 0.55-1.85; P = .98). Conclusions: The available data suggest that PPA repair via EVR is a safe alternative to OR, but that short-term graft thrombosis and reintervention rates are significantly greater for the former approach. Moreover, few studies to date have compared these techniques and those that were largely retrospective in nature with relatively low-quality evidence, making it difficult to make definitive statements regarding the relative safety and efficacy of these 2 repair strategies. Additional population-based large-scale studies are therefore essential in order to conduct a robust evaluation of the safety and utility of EVR as an alternative to OR for PPA repair.